Fabrication of Schottky Diodes on Zn-polar BeMgZnO/ZnO Heterostructure Grown by Plasma-assisted Molecular Beam Epitaxy - Ding, Kai (J Vis Exp, 2018)
Heterostructure field effect transistors (HFETs) utilizing a two dimensional electron gas (2DEG) channel have a great potential for high speed device applications. Zinc oxide (ZnO), a semiconductor with a wide bandgap (3.4 eV) and high electron saturation velocity has gained a great deal of attention as an attractive material for high speed devices. Efficient gate modulation, however, requires high-quality Schottky contacts on the barrier layer. In this article, we present our Schottky diode fabrication procedure on Zn-polar BeMgZnO/ZnO heterostructure with high density 2DEG which is achieved through strain modulation and incorporation of a few percent Be into the MgZnO-based barrier during growth by molecular beam epitaxy (MBE). To achieve high crystalline quality, nearly lattice-matched high-resistivity GaN templates grown by metal-organic chemical vapor deposition (MOCVD) are used as the substrate for the subsequent MBE growth of the oxide layers. To obtain the requisite Zn-polarity, careful surface treatment of GaN templates and control over the VI/II ratio during the growth of low temperature ZnO nucleation layer are utilized. Ti/Au electrodes serve as Ohmic contacts, and Ag electrodes deposited on the O(2) plasma pretreated BeMgZnO surface are used for Schottky contacts.